Novel technique in simplifying the fabrication process and ind improving the reflection coefficient of the linear polarized radial line slot array (LP-RLSA) antennas - Teddy Purnamirza (Kemntran Agama RI, 2012)
xiv, 209 hlm. ; ill. ; 24 cm.